Inovasi Alat Praktikum Pembelajaran Geografi - Agus, Mujahidin (Jurnal Nispatti, 2023)
The need for practical tools in presenting teaching materials, especially about natural phenomena – the process of cloud formation, rain, wind, differences in air pressure, and tornadoes – which are difficult to observe or witness the process of occurrence in nature. The author made and used a simple teaching aid from his own innovation to meet these demands. The teaching aid was made from used jars and plastic bottles. This tool can be used by students in class. As a result, geography learning in class X of SMA Negeri 3 Palopo gave good results. The level of student activity and independence in discovering the substance of the teaching material by themselves was very high compared to not using practical tools. Student learning outcomes also increased. Student scores in Class X-G and Class X-H successfully increased on average from 77.48 to 83.78. The results of the t-test to test the difference between the two values ​​produced a t-count value of 9.220 which was much greater than the t-table value of only 1.645 with an α of 0.05. The obstacle faced in implementing the practice using the tool was the rather long manufacturing time. However, this obstacle can be overcome by having students make the tools at home. Alternative developments can be made by modifying or designing other practical tools using the same materials.